Greenhouse Gases and Global Change: A Challenge for Canadian Geoscience - Piper, David (Geoscience Canada, 2006)
SUMMARY Climate change is the most pressing societal issue of our time. The Canadian geological community is deeply divided as to whether or not anthropogenic carbon dioxide is the principal driver of the global warming that we see around us. As geologists, we have the scientific understanding to be effective stewards of Planet Earth and thus have a critical role to play in the climate change debate. Many of the basic scientific principles in this debate, however, are more a matter of atmospheric physics than classical geology: this may be one reason why so much uncertainty continues in the geological community. Also, we have a professional responsibility to inform ourselves and our colleagues beyond the level of knowledge of the general public. We must apply the precautionary principle in assessing the response of the Earth to human activity. We should learn from the engineering and medical communities that our students should be well educated in fundamental principles and that a balanced assessment of issues should be presented to the public and decision-makers. The scientific debate over climate change should be carried on at mainstream meetings and in the peer-reviewed literature.